Upaya Kepala Sekolah Meningkatkan Kedisiplinan Kehadiran Guru Mengajar di Kelas Melalui Penerapan Reward and Punishment di SDN 002 Babulu - Lailil Muhanah (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The problem behind this school action research was the presence of teachers in the classes at SD Negeri 002 Babulu. Improving the quality of education in schools really depends on several factors, one of which is teacher discipline in teaching. The aim of this research is; (1) to find out whether the application of rewards and punishments can increase attendance discipline in class, (2) to measure the extent to which teacher attendance discipline increases in teaching in class after implementing rewards and punishments. , (3) describes the process of increasing classroom attendance discipline after implementing rewards and punishments. This type of research is a two-cycle school activity research. Each cycle consists of planning, implementation, observation and reflection. From the research results it is known that the percentage of teachers who arrive less than 10 minutes before class starts is 10%, increasing to 50% in cycle I and again to 70% in cycle II. Exceeding the target set, namely 70% of teachers were late for class by up to 10 minutes. Meanwhile, the percentage of teachers who took part in learning based on the RPP in the pre-cycle was 0%, meaning that there were 10 department teachers who abandoned the RPP announced before learning, in cycle I. 50% increased due to the increase in the number of teachers. regarding participation in teaching their discipline, leaving lessons according to schedule and returning 100% in cycle II. This achieved the target set, namely 100% of teachers leaving the classroom according to the RPP. Based on the research results, it can be concluded that the application of rewards and punishment to teachers can improve the discipline of teacher attendance at SD Negeri 002 Babulu.